Interstitial pregnancy – from diagnosis to treatment: case report and literature review - Stoyanova, Nikoleta; Yordanov, Angel; Popovski, Nikola (Menopause Review/Przegląd Menopauzalny, 2025)
Interstitial pregnancy (IP) is a rare kind of tubal pregnancy, which occurs in 2–4% of all ectopic pregnancies. It occurs as a result of implantation of the gestational sac in the proximal intramural part of the fallopian tube. Risk factors include the following: pregnancy conceived after assisted reproductive technologies, ipsilateral salpingectomy, previous ectopic pregnancy, congenital tubal and uterine malformations, pelvic inflammatory disease, and the presence of an intrauterine device. Given the rare and complex nature of interstitial pregnancies, diagnosis and management are difficult. Transvaginal ultrasound is the most specific instrumental method for early diagnosis that can decrease possible complications, such as rupture, severe haemorrhage, and risk of future infertility in the case of misdiagnosis. There are various surgical and non-surgical methods for the treatment of interstitial pregnancy. The method of choice depends on gestational age, whether the pregnancy is intact or ruptured, and the patient’s desire for future fertility. However, surgery is still the main option for the treatment of IP because it offers definitive treatment. Generally, complicated IP is associated with high rate of mortality due to delayed diagnosis and treatment. We present a case report related to a multiparous woman with amenorrhoea and ultrasound findings corresponding to sonographic criteria for interstitial pregnancy. Laparoscopy was performed, which confirmed the diagnosis. Bilateral salpingectomy and right cornual resection were performed because the patient had no intention for future pregnancies.